2018
DOI: 10.1016/j.dci.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Siglecs: A journey through the evolution of sialic acid-binding immunoglobulin-type lectins

Abstract: Siglecs (sialic acid-binding immunoglobulin-type lectins) are a family of immune regulatory receptors predominantly found on the cells of the hematopoietic system. A V-set Ig-like domain mediates the recognition of different sialylated glycoconjugates, which can lead to the activation or inhibition of the immune response, depending on the involved Siglecs. Siglecs are categorized into two subgroups: one including all CD33-related Siglecs and the other consisting of Siglec-1 (Sialoadhesin), Siglec-2 (CD22), Sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 106 publications
2
95
0
1
Order By: Relevance
“…Lehmann et al suggested that these motifs are involved in signal transduction and contribute to biological functions different from those described for mammalian MAG [16]. Furthermore, our previous sequence analysis [15] confirmed the presence of ITIMs in coelacanth, while almost all investigated higher vertebrates were ITIM-negative. Consequently, the ITIM motif seems to be an ancestral feature that has persisted in most Siglecs but was lost during the evolution of higher vertebrates [15,16].…”
Section: Sequence Comparison Of Siglec4 (Mag)supporting
confidence: 76%
See 2 more Smart Citations
“…Lehmann et al suggested that these motifs are involved in signal transduction and contribute to biological functions different from those described for mammalian MAG [16]. Furthermore, our previous sequence analysis [15] confirmed the presence of ITIMs in coelacanth, while almost all investigated higher vertebrates were ITIM-negative. Consequently, the ITIM motif seems to be an ancestral feature that has persisted in most Siglecs but was lost during the evolution of higher vertebrates [15,16].…”
Section: Sequence Comparison Of Siglec4 (Mag)supporting
confidence: 76%
“…The expression of MAG is restricted to Schwann cells and oligodendrocytes. The dimerization of MAG is essential for specific axon-myelin spacing (9-12 nm) and strongly depends on the glycosylation pattern of MAG [15,35,54,55]. Therefore, we also inspected potential N-glycosylation sites of the MAG sequences from maraena whitefish and Atlantic salmon.…”
Section: Sequence Comparison Of Siglec4 (Mag)mentioning
confidence: 99%
See 1 more Smart Citation
“…Control of neutrophil ROS production is at least partly mediated by CD33-related subfamily of Siglecs (Sialic acid-binding Ig-like lectins) 28,[32][33][34][35][36][37][38][39] encoded in the CD33rSIGLEC gene cluster, and referred to as CD33rSiglecs. [40][41][42][43][44] Consistent with the phylogenetic distribution of sialic acids in the deuterostome lineage of animals, this gene cluster only occurs vertebrates. The CD33rSiglecs recognize endogenous sialylated glycans as SAMPs 29 and modulate myeloid cell lineage reactivity.…”
Section: Introductionmentioning
confidence: 91%
“…Siglecs include (a) CD33-related Siglecs and (b) Siglec-1 (Sialoadhesin), Siglec-2 (CD22), Siglec-4 (myelin-associated glycoprotein, MAG), and Siglec-15. Phylogenetic studies in higher vertebrates including fishes, amphibians, birds, reptiles and mammals have revealed that Siglecs are conserved in evolution [316]. A loss of Siglec genes in rodents have been reported.…”
Section: Siglecsmentioning
confidence: 99%